Enhancing Students’ Spatial Ability and Mathematical Resilience in Trigonometry Through the Realistic Mathematics Education (RME) Approach with Clinometer Media - Gilang Fathurrohman Fattah; Wahyu Lestari; Athar Zaif Zairozie (Jurnal Pendidikan Matematika (JPM), 2025)
This study aims to measure and analyze the effect of the RME approach assisted by a clinometer on students' spatial abilities and mathematical resilience in trigonometry. The sample of this study was 60 students of SMAN 1 Maron, consisting of 30 students of class XA as the control class and 30 students of class XB as the experimental class. This research used a quantitative method, a quasi-experimental design, and a purposive sampling technique. Learning sessions in this study were conducted as many as 4 meetings for 2 hours of lessons in each meeting. Data analysis was conducted using Independent Sample T-Test and N-Gain test. The tests for normality and homogeneity indicated that the data followed a normal distribution and exhibited homogeneity. The results of the Paired Sample T-Test showed a significant improvement in the experimental class, with a Sig. (2-tailed) value of 0.000 (p < 0.01), indicating a substantial effect on students' spatial ability and mathematical resilience. The N-Gain scores for the experimental class were 60.08 for spatial ability and 57.90 for mathematical resilience, categorizing the intervention as effective. These results indicate that using the RME approach alongside clinometer media improves students' spatial skills and mathematical resilience in trigonometry learning.